Perbandingan Kandungan Nutrisi Tudung dan Batang Jamur Shiitake pada Perkebunan Jamur di Cibodas, Indonesia - Donowati Tjokrokusumo; Netty Widyastuti; Henky Isnawan (Fakultas Farmasi Universitas Pancasila, 2005)
Mushroom has been accepted as human food since ages or hundred years ago. Shiitake (Lentinus edodes) is one of an edible mushrooms which has fiber, carbohydrate and protein higher than Oyster (Pleurotus ostreatus). The nutrition of the fruit body and the stem has been analyzed. Comparison of the fruit body and the stem have been conducted for protein, carbohydrate, and the fiber contents. Protein content in the fruit body is higher than in the stem. However the fiber and the carbohydrate contents are higher in the stem than in their fruit body. The amount of protein, carbohydrate and fiber in the fruit body is 31.07%, 15.9% and 7.08% dry weight consecutively. And the amount of protein, carbohydrate and fiber in the stem 12.01%, 19.46% and 10.3% dry weight successively have been observed in this study. Combination of fruit body and stem would be good for human diet in the future.